2012
DOI: 10.1155/2012/936128
|View full text |Cite
|
Sign up to set email alerts
|

A National Baseline Prevalence Survey of Schistosomiasis in the Philippines Using Stratified Two-Step Systematic Cluster Sampling Design

Abstract: For the first time in the country, a national baseline prevalence survey using a well-defined sampling design such as a stratified two-step systematic cluster sampling was conducted in 2005 to 2008. The purpose of the survey was to stratify the provinces according to prevalence of schistosomiasis such as high, moderate, and low prevalence which in turn would be used as basis for the intervention program to be implemented. The national survey was divided into four phases. Results of the first two phases conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 12 publications
1
66
1
Order By: Relevance
“…We used S. japonicum infection data collected during the most recent national schistosomiasis surveys conducted in 2008 (Leonardo et al, 2008, 2012) (Supplementary Data S1). The surveys were divided into four phases: phase 1 for Mindanao (excluding Maguindanao), phase 2 for the Visayas, phase 3 for Luzon and phase 4 for Maguindanao.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used S. japonicum infection data collected during the most recent national schistosomiasis surveys conducted in 2008 (Leonardo et al, 2008, 2012) (Supplementary Data S1). The surveys were divided into four phases: phase 1 for Mindanao (excluding Maguindanao), phase 2 for the Visayas, phase 3 for Luzon and phase 4 for Maguindanao.…”
Section: Methodsmentioning
confidence: 99%
“…The most recent national parasite survey in The Philippines concluded that S. japonicum infection was endemic in 28 of the 80 provinces of the country (Leonardo et al, 2008, 2012). An estimated 6.7 million people are considered at risk, with 1.8 million estimated to be infected (Leonardo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 12 million people living in 28 endemic provinces located in 12 different regions of the country are at risk of infection ( Fig. 2) [19,20]. Overall, a total of 190 municipalities and 20 cities are affected by the infection.…”
Section: History Of Mda For Schistosomiasis Control In the Philippinesmentioning
confidence: 99%